End‐of‐life priorities of older adults with terminal illness and caregivers: A qualitative consultation - Lewis, Ebony T. (Health Expect, 2019)
BACKGROUND: As older adults approach the end‐of‐life (EOL), many are faced with complex decisions including whether to use medical advances to prolong life. Limited information exists on the priorities of older adults at the EOL. OBJECTIVE: This study aimed to explore patient and family experiences and identify factors deemed important to quality EOL care. METHOD: A descriptive qualitative study involving three focus group discussions (n = 18) and six in‐depth interviews with older adults suffering from either a terminal condition and/or caregivers were conducted in NSW, Australia. Data were analysed thematically. RESULTS: Seven major themes were identified as follows: quality as a priority, sense of control, life on hold, need for health system support, being at home, talking about death and competent and caring health professionals. An underpinning priority throughout the seven themes was knowing and adhering to patient's wishes. CONCLUSION: Our study highlights that to better adhere to EOL patient's wishes a reorganization of care needs is required. The readiness of the health system to cater for this expectation is questionable as real choices may not be available in acute hospital settings. With an ageing population, a reorganization of care which influences the way we manage terminal patients is required.